PERAN PEMKOT SAMARINDA DALAM MEWUJUDKAN TAMAN SEJATI SEBAGAI RUANG TERBUKA HIJAU YANG BERKEARIFAN LOKAL - Robin Dana; Sadam Kholik, Aullia Vivi Yulianingrum (JOURNAL OF LAW AND NATION, 2024)
The importance of the existence of Green Open Space (RTH) in urban areas is undeniable. From the view of many experts, the existence of Green Open Space (RTH) is important for improving air quality in urban areas, regulating urban microclimate, sweeping dust in urban areas, reducing noise, supporting water management systems in urban areas, supporting germplasm preservation, as well as supporting urban use and management. land preservation. The aim of this research is to find synchronization of the role of the Samarinda City Government's policies in efforts to realize Taman Sejati as a Green Open Space with local wisdom for the Samarinda City Community. The local wisdom of living communities needs to be actualized and strengthened in the form of regulations by the Regional Government of Samarinda City in the form of regional government policies so that it can be accepted in plural and heterogeneous society. Taman Sejati as a green open space that embodies local wisdom can be used as a model for protecting, maintaining and preserving the natural resources of Samarinda City.